ChemInform Abstract: Facile Synthesis of Multifunctional Pyrrole[2, 1‐a]isoquinolin‐3(2H)‐ones via Sulfa‐Michael‐Triggered One‐Pot Reactions. Issue 25 (2nd June 2016) - Qin, Tian‐You; Cheng, Lu; Jang, Ho‐Chol; Zhang, Sean Xiao‐An; Liao, Wei‐Wei
Abstract: Sulfur‐containing pyrroloisoquinolinones are rapidly synthesized by a general method involving a sulfa‐Michael‐triggered tandem reaction and subsequent lactamization reaction.